2015
DOI: 10.1002/fsn3.302
|View full text |Cite
|
Sign up to set email alerts
|

The chemical quality of frozen Vietnamese Pangasius hypophthalmus fillets

Abstract: The aim of the present study was to evaluate the chemical quality parameters regarding frozen Pangasius hypophthalmus specimens from Vietnam. The proximate composition, pH, ammonia, biogenic amines (BAs), total mercury (Hg), malondialdehyde (MDA), and polyphosphate were determined. The moisture, protein, lipid and ash values were between 83.83–85.59, 12.51–14.52, 1.09–1.65, and 0.76–2.38 g 100 g−1, respectively. Fraud by excessive polyphosphate addition was detected in 30% of the samples whereas Hg above the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
4
27
0
1
Order By: Relevance
“…The results demonstrated that anchovy fillets are characterised by higher nutrient concentrations than Vietnamese pangasius; in particular, their lipid content is five times higher than that of pangasius fillets. According to science-based nutrition standards, the anchovy lipid content is equivalent to that of low-fat meat (2-4%), whereas the content determined in pangasius fillets is similar to that found in lean meat (<2%) [32]. Total SFA, MUFA, and PUFA concentrations varied significantly between the two species.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The results demonstrated that anchovy fillets are characterised by higher nutrient concentrations than Vietnamese pangasius; in particular, their lipid content is five times higher than that of pangasius fillets. According to science-based nutrition standards, the anchovy lipid content is equivalent to that of low-fat meat (2-4%), whereas the content determined in pangasius fillets is similar to that found in lean meat (<2%) [32]. Total SFA, MUFA, and PUFA concentrations varied significantly between the two species.…”
Section: Discussionmentioning
confidence: 87%
“…The lower protein content determined in Vietnamese pangasius has previously been described in fillets sold on different European markets (e.g., Italy [34]; Poland [35]; Germany [36]). According to [37] and similar studies [32,[34][35][36], fish with high amounts of protein must contain greater than 15%. Furthermore, processing often involves the addition of large amounts of polyphosphates, which may increase water-binding capacity, thus reducing protein content [32,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to CBI (2015), Vietnam is the main Pangasianodon producer, followed by Indonesia. In Indonesia production is reported to reach 400,000 tons per year, much of it for domestic consumption, but the fish has also been widely exported from Indonesia to various countries in Europe due to the acceptability of the product and its low price (Ciardullo et al 2008;Guimarães et al 2016). The success and significant increase in striped catfish production have received attention not only from farmers and investors but also from researchers seeking to increase productivity through strategies to improve growth rates, health performance, and the immune system of the fish.…”
Section: Introductionmentioning
confidence: 99%